Cooperation model between the management accounting system and the design system - Tatiana; Orlov, Evgeniy; Smolyakov, Oleg; Somkin, Igor; Prokin, Vitaliy (International Journal of Psychosocial Rehabilitation, 2020)
A large number of global innovative projects have become implemented nowadays. This article is devoted to the initial stage of testing us the proposed hypothesis existence of an optimal interaction model between the management accounting system and the design system of the innovation project. Such research methods as formalization, hypothetical-deductive method, abstraction, idealization, analysis, synthesis, system approach, specialized survey, document analysis, dialogue was used at the first stage of exploration. The results were received studied in the participation of a representative group of three enterprises. Indirect confirmation of the proposed hypothesis was obtained in addition. It found some problems of cooperation between the management accounting system and the engineering system at the considered enterprises. These cases have become low-level business processes and bad project management. The first stage results allow us to make a guess about the possibility of a further test of the proposed hypothesis to prove it. Output data obtained in accordance with proposed method of allow us to make an assumption, about possibility of implementing subsequent stages of study in order to fully test of hypothesis.